A comprehensive study on ultrasonic deactivation of opportunistic pathogen Saccharomyces cerevisiae in food processing: From transcriptome to phenotype. (1st December 2022) - Liu, Junyan; Huang, Tengyi; Hong, Wei; Peng, Fang; Lu, Zerong; Peng, Gongyong; Fu, Xin; Liu, Gongliang; Wang, Zhi; Peng, Qingmei; Gong, Xiangjun; Zhou, Lizhen; et al.
Abstract: This study aimed to investigate morphological changes and regulatory mechanism of opportunistic pathogen Saccharomyces cerevisiae upon ultrasonic. Ultrasound intensities (0/102.8/288 W, 10 min) were applied on S. cerevisiae (OD600 = 0.1), with morphology monitored by inverted microscopy, atomic force microscopy, digital holographic microscopy, and transmission electron microscopy. Under high-power ultrasound (HPUL) treatment (288 W, 10 min), cells maintained chromosomal DNA integrity, with a large proportion of differentially expressed genes identified by RNA-seq. Osmotic pressure was firstly induced to disrupt ATPase and ion homeostasis, then reactive oxygen species and physical and chemical effects during cavitation were generated as key factors to inactivate S. cerevisiae cells. Besides, ergosterol of plasma membrane was changed, improving plasma membrane permeability for H2 O2 . Accumulation of H2 O2 induced activation of stress response. During short-term HPUL, yeast down-regulated ribosome synthesis to prevent accumulation of ultrasound-induced dysfunctional protein. However, loss of protein synthesis caused insufficient protein supplement for growth and stress response during long-term HPUL, leading to cell wall injury. As concluded, HPUL induced stress response and changed cell metabolism of S. cerevisiae, potentially resulting in the failure of deactivation. This study will guide in proper treatment of opportunistic pathogen S. cerevisiae in food processing especially in ultrasonic application. Graphical abstract: The mechanism of ultrasound on the S. cerevisiae morphology and gene transcription. Image 1 Highlights: Monitored by IM, AFM, DHM, TEM, HPUL treated yeast cells surround by FS and maintain DNA integrity. Reactive oxygen species and cavitation induced by HPUL is the first factor to inactivate yeast cells. Ergosterol of plasma membrane changed by HPUL and accumulation of intracellular H2 O2 induce stress responses. HPUL potentially improve yeast cell metabolism resulting in the failure of its deactivation in food processing.